Implementasi Kebijakan Ekonomi Pariwisata dan Perwujudan Pemberdayaan Masyarakat di Kota Batu - Magistyo P Priambodo (Universitas Negeri Malang, 2015)
This research was to describe the government implementation of economic tourism policy and its impact on community through empowerment program in Batu City. As one of new autonomus region in east java, Batu City use geographic advantages that is concern in tourism sector to raise region economic development. Using qualitative fenomenology approach to analize. There are two strategic policy in Batu City that implementing in tourism development, first is conventional paradigm policy and then sustainable paradigm policy. Each implementation of the policy has brought different consequences and impact on development in Batu City. As a result, emerging programs aimed at improving the development of tourism to reduce conflicts that can occur and to increase community participation as empowerment through community based tourism concept, increasing the role of local SMEs and creating city branding called